2015
DOI: 10.1111/jcpe.12444
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated growth factor in the treatment of adjacent multiple gingival recessions: a split‐mouth randomized clinical trial

Abstract: The use of CGF in combination with CAF did not provide additional benefits in RD, CRC and MRC. This study suggests that use of CGF + CAF may increase the success of GRs because of a significant increase in KGW and GT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 37 publications
7
49
0
Order By: Relevance
“…Electronic and hand searches yielded 540 articles, of which 12 were selected (2) for full-text evaluation after screening their titles and abstracts. Two articles [28,29] were further excluded and reasons are listed in (Figure 1). The k value for inter-reviewer agreement for potentially relevant articles was 0.95 for full text articles reviewing; indicating an ''almost perfect'' agreement between the two reviewers [30].…”
Section: Resultsmentioning
confidence: 99%
“…Electronic and hand searches yielded 540 articles, of which 12 were selected (2) for full-text evaluation after screening their titles and abstracts. Two articles [28,29] were further excluded and reasons are listed in (Figure 1). The k value for inter-reviewer agreement for potentially relevant articles was 0.95 for full text articles reviewing; indicating an ''almost perfect'' agreement between the two reviewers [30].…”
Section: Resultsmentioning
confidence: 99%
“…Doğan, et al 14 (2015) reported that CGF treatment did not show any additive effect on the RC results of the CAF procedure. The authors 14 suggested CGF application with CAF might increase the long-term stability of RC due to increasing KTW (0.58 mm) and KTT (0.32 mm), which caused a better attachment gain. Increases of 0.14 mm/0.28 mm, respectively, were observed in the KTW/KTT at the sixth month for the CGF group.…”
Section: The Median Hi Values Significantly Increasedmentioning
confidence: 99%
“…That study showed CGF with CAF surgery increased the keratinized tissue width (KTW) and keratinized tissue thickness (KTT) and may prevent postoperative relapse after the CAF procedure. 14…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, with excluding case series (without a control group), 18 studies on bone regeneration and six studies on regeneration of other tissues are listed in Tables and . Two articles were randomized clinical trials and one was a cohort study in which the treated pathologies were peri‐implantitis, guided tissue regeneration (GTR), and gingival recessions (Bozkurt Dogan et al, ; Isler et al, ; Lei et al, ). Most studies stated improvement of tissue healing or regeneration in the presence of CGF, yet three studies investigating its effect on peri‐implantitis, implant stability, and immediate implants reported no significant difference or lower effect of CGF (Isler et al, ; Özveri Koyuncu, İçpınar Çelik, et al, ; Yang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, with excluding case series (without a control group), 18 studies on bone regeneration and six studies on regeneration of other tissues are listed inTables 4 and 5. Two articles were randomized clinical trials and one was a cohort study in which the treated pathologies were peri-implantitis, guided tissue regeneration (GTR), and gingival recessions(Bozkurt Dogan et al, 2015;Isler et al, 2018;Lei et al, 2019).…”
mentioning
confidence: 99%